Impact of olfactory and auditory priming on the attraction to foods with high energy density. (1st December 2015) - Chambaron, S.; Chisin, Q.; Chabanet, C.; Issanchou, S.; Brand, G.
Abstract: Recent research suggests that non-attentively perceived stimuli may significantly influence consumers' food choices. The main objective of the present study was to determine whether an olfactory prime (a sweet-fatty odour) and a semantic auditory prime (a nutritional prevention message), both presented incidentally, either alone or in combination can influence subsequent food choices. The experiment included 147 participants who were assigned to four different conditions: a control condition, a scented condition, an auditory condition or an auditory-scented condition. All participants remained in the waiting room during15 min while they performed a 'lure' task. For the scented condition, the participants were unobtrusively exposed to a 'pain au chocolat' odour. Those in the auditory condition were exposed to an audiotape including radio podcasts and a nutritional message. A third group of participants was exposed to both olfactory and auditory stimuli simultaneously. In the control condition, no stimulation was given. Following this waiting period, all participants moved into a non-odorised test room where they were asked to choose, from dishes served buffet-style, the starter, main course and dessert that they would actually eat for lunch. The results showed that the participants primed with the odour of 'pain au chocolat' tended to choose more desserts with high energy density (i.e., a waffle) than the participants in the control condition (p = 0.06). Unexpectedly, the participants primed with the nutritional auditory message chose to consume more desserts with high energy density than the participants in the control condition (p = 0.03). In the last condition (odour and nutritional message), they chose to consume more desserts with high energy density than the participants in the control condition (p = 0.01), and the data reveal an additive effect of the two primes. Highlights: We study if an incidental sweet-fatty odour influences food choices. We study if an incidental auditory nutritional message influences food choices. An incidental nutritional message increases choices of a high-energy dessert. A sweet-fatty odour with a nutritional message increases choices of a high-energy dessert.